Pragmatyka wypowiedzi artystycznej w satyrach Mariana Hemara - Binek, Paweł (ANNALES UNIVERSITATIS PAEDAGOGICAE CRACOVIENSIS. STUDIA LINGUISTICA, 2013)
The aim of the article is to present the circumstances of creating and understanding the satires by Marian Hemar. The first section of this paper focuses on the formula of composing the satires. The second section presents the pragmatics of the satire. The third section looks at the literary and linguistic aspects of the satires by Hemar.